1995
DOI: 10.1080/00288233.1995.9513124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herbage species and feeding level on internal parasites and production performance of grazing lambs

Abstract: The effect of internal parasites on the performance of lambs grazing different forage species was examined in two experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 15 publications
(14 reference statements)
4
42
2
Order By: Relevance
“…Lucerne has been shown to give higher lamb growth rates than grass-based pastures (Nicol & McLean 1970;Scales et al 1995). However, in the present experiment its use did not improve ewe or lamb liveweights, nor did it assist in reducing lamb worm burdens.…”
contrasting
confidence: 48%
See 3 more Smart Citations
“…Lucerne has been shown to give higher lamb growth rates than grass-based pastures (Nicol & McLean 1970;Scales et al 1995). However, in the present experiment its use did not improve ewe or lamb liveweights, nor did it assist in reducing lamb worm burdens.…”
contrasting
confidence: 48%
“…Moss & Vlassoff (1993) found that ryegrass-and prairie grass-based swards contained more nematode larvae than did lucerne, which in turn contained more than chicory. A similar observation was made by Scales et al (1995) in a lamb grazing experiment which compared a pasture with low endophyte ryegrass, cocksfoot, and tall fescue with a pasture containing lucerne and chicory.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Using different pasture species offers a means of influencing the microclimate within the sward and therefore the larval population (Moss & Vlassoff 1993;Niezen et al 1998), and the number ingested by grazers (Knapp 1964;Scales et al 1995).…”
Section: Introductionmentioning
confidence: 99%